Plant presence reduces root and shoot litter decomposition rates of crops and wild relatives - Barel, Janna M.; Kuyper, Thomas W.; de Boer, Wietse; De Deyn, Gerlinde B. (Plant and soil, 2019)
Aims Roots contribute greatly to carbon cycling in agriculture. Measuring aboveground litter decomposition could approximate belowground turn-over if drivers of decomposition, f.e. litter traits and plant presence, influence shoot and root decomposition in a comparable manner. We tested coordination of above- and belowground litter traits and decomposition rates for six pairs of crops and closely related wild plants and studied the influence of plant presence on decomposition. Methods Above- and belowground traits were measured, compared and related to decomposition rates. Shoot and root litters were incubated in presence of the same plant species as the litter species (own) or in presence of two other plant species (a grass or forb). Results Shoots decomposed 1.43–1.98 times faster than (resp.) wild plant and crop roots. Decomposition correlated negatively with litter carbon and lignin concentrations, except crop root decomposition which correlated negatively with nitrogen concentration. Unexpectedly, plant presence reduced litter decomposition, with strongest effects for root litters in presence of forbs. Conclusions Carbon cycling might be slower than predicted solely based on shoots decomposition rates, especially in presence of growing plants. While root decomposition of wild plants can be approximated by shoot decomposition, crop shoots are a poor proxy for crop root decomposition.